2016
DOI: 10.1186/s40792-016-0148-3
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset diaphragmatic hernia after percutaneous radiofrequency ablation of hepatocellular carcinoma: a case study

Abstract: Percutaneous radiofrequency ablation (RFA) is widely used as an effective treatment of liver tumors. Several reported complications associated with RFA are due to thermal damage of neighboring organs. The present report presents a case of diaphragmatic hernia associated with RFA and hepatocellular carcinoma (HCC). A 72-year-old woman with S5 and S8 HCCs was treated repeatedly with RFA and transcatheter arterial chemoembolization for 3 years. After the third course of RFA to target the recurring S5 HCC, acute a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…In this case, a DH with acute intestinal obstruction and necrosis occurred 52 months after RFA, after emergency surgery, the patient recovered and was discharged successfully. According to previous literature reports [11][12][13][14][15][16][17][18][19][20][21][22] , the occurrence time of DH after RFA is 7-96 months (median 18 months), combined with our case, DH is considered to be a long-term complication of RFA, which is consistent with the occurrence mechanism of acquired diaphragmatic hernia, suggesting that for patients after RFA, the occurrence of DH should be vigilant during long-term follow-up.…”
Section: Discussionsupporting
confidence: 86%
“…In this case, a DH with acute intestinal obstruction and necrosis occurred 52 months after RFA, after emergency surgery, the patient recovered and was discharged successfully. According to previous literature reports [11][12][13][14][15][16][17][18][19][20][21][22] , the occurrence time of DH after RFA is 7-96 months (median 18 months), combined with our case, DH is considered to be a long-term complication of RFA, which is consistent with the occurrence mechanism of acquired diaphragmatic hernia, suggesting that for patients after RFA, the occurrence of DH should be vigilant during long-term follow-up.…”
Section: Discussionsupporting
confidence: 86%
“…There was no description of late-phase diaphragmatic hernia in three studies [5] [6] [7]. However, in some reports, cases of late-phase diaphragmatic hernia required an emergency surgery because of a strangulated intestine [8] [10]- [18]. Diaphragmatic hernia after RFA seems to be caused by thermal damage to the diaphragm.…”
Section: Discussionmentioning
confidence: 99%
“…Tabrizian et al reported that 5.4 % of 55 patients who underwent hepatic resection with concomitant diaphragmatic resection and repair developed iatrogenic DH [ 1 ]. Fragility of the diaphragm due to thermal damage or resection can cause iatrogenic DH [ 1 , 10 ], and there is no way to prevent such DH from occurring other than to ensure intraoperative diaphragmatic repair. Most of the reported iatrogenic DH cases presented with stomach or intestinal incarceration were symptomatic and required surgical treatment [ 1 , 10 ].…”
Section: Case Presentationmentioning
confidence: 99%
“…Fragility of the diaphragm due to thermal damage or resection can cause iatrogenic DH [ 1 , 10 ], and there is no way to prevent such DH from occurring other than to ensure intraoperative diaphragmatic repair. Most of the reported iatrogenic DH cases presented with stomach or intestinal incarceration were symptomatic and required surgical treatment [ 1 , 10 ]. The anatomic location of the liver minimizes the possibility of a right-sided intestinal or stomach incarceration, and there is no report of the surgical indication for iatrogenic hepatic herniation alone.…”
Section: Case Presentationmentioning
confidence: 99%